PENGARUH PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS: SYSTEMATIC LITERATURE REVIEW - Niken Shofiana Dewi; Dadang Juandi (IKIP Siliwangi, 2023)
This study aims to determine whether or not there is an effect of applying an open-ended approach on students' mathematical creative thinking abilities. The research method used is a Systematic Literature Review with the PRISMA protocol. The search for research articles was carried out within the 2015-2022 publication year and indexed by Google Scholar, Semantic Scholar, and ERIC. The analysis technique used is grouping, data analysis, and drawing conclusions. After that, the following results are obtained: (1) There is an effect of the open-ended approach on students' mathematical creative thinking abilities. (2) The uses of technology in applying open-ended approach can be used to improve mathematical creative thinking skills, for example, animated videos. (3) The diversity (heterogeneity) of studies relate to the effect of open-ended approach on students' mathematical creative thinking abilitiesy can be reviewed based on the year of publication, education level, the sample size of the experimental class, the status of technological assistance, and combination of learning.